Acrobat 6 and PDF solutions - Tally, Taz (Sybex, Inc., 2004)
Acrobat 6 and PDF Solutions offers expert instruction on putting this complex tool to good use. With his characteristic enthusiasm, acclaimed instructor and author Taz Tally introduces you to key features and techniques, then leads you through real-world tutorials that reinforce the material. In addition to a complete tour of Acrobat 6, you get an in-depth guide to creating PDF documents and working with Distiller and other PDF creation workflows. Productivity tips and automations throughout help you work faster and more accurately.